2002
DOI: 10.1002/sia.1276
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of aluminium metal–matrix composites by cerium conversion coatings

Abstract: Effect of cerium pretreatment on the corrosion inhibition characteristics of AA6061 T6 alloy-10% Al 2 O 3 metal-matrix composite was investigated in aerated 3.5% NaCl solution after different immersion times ranging between 1 and 60 days at room temperature. Series of specimens were prepared under the following conditions: as-polished; directly treated in CeCl 3 ; alkaline etching followed by CeCl 3 treatment; immersion in boiling water followed by CeCl 3 treatment; and alkaline etching followed by immersion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Lightweight aluminum alloys matrices reinforced with silicon carbide (SiC) particles possess higher tensile strength and ductility at 300-400 8C and lower coefficient thermal expansion, but the use of these materials has been limited partially because they suffer from localized corrosion in the form of pitting in solutions containing chloride [6][7][8][9]. Aluminum alloys are usually chromated, painted, oxidized, or anodized in chromic, phosphoric, or sulfuric acid solutions to improve their corrosion resistance under a variety of aggressive atmospheric conditions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight aluminum alloys matrices reinforced with silicon carbide (SiC) particles possess higher tensile strength and ductility at 300-400 8C and lower coefficient thermal expansion, but the use of these materials has been limited partially because they suffer from localized corrosion in the form of pitting in solutions containing chloride [6][7][8][9]. Aluminum alloys are usually chromated, painted, oxidized, or anodized in chromic, phosphoric, or sulfuric acid solutions to improve their corrosion resistance under a variety of aggressive atmospheric conditions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Hamdy also reported that the direct treatment cerium solution does not provide good corrosion protection for aluminum alloys. 41 They also confirmed the presence of localized corrosion even after a long cerium treatment. The mechanism of corrosion inhibition due to cerium depends on the incorporation of cerium ions through the pores of the Al oxide layer to block the active surface sites ͑cathodic inhibitor͒.…”
Section: Impedance Methodsmentioning
confidence: 73%
“…The mechanism of corrosion inhibition due to cerium depends on the incorporation of cerium ions through the pores of the Al oxide layer to block the active surface sites ͑cathodic inhibitor͒. 41 Jakab and Scully established that the corrosion inhibition of AA 2024-T3 is possible with metal ions released from an amorphous Al-Co-Ce alloy located in close proximity to the defect. 42 They explained that protection of alloys exposed at coating defects is demonstrated by inhibitor ion release in addition to barrier function and sacrificial cathodic protection.…”
Section: Impedance Methodsmentioning
confidence: 99%
“…The most probable source of silicon is the matrix, where silicon is mainly concentrated at the interface between the matrix and alumina particles. Another source is the dissolution of silicon from glass during the pickling process by KOH [22,23,25].…”
Section: Resultsmentioning
confidence: 99%
“…However, data reported to date suggest that conversion coatings based on cerium, have various disadvantages such as nonuniform distribution [16,[19][20][21]. In the first part of this work, Hamdy et al [22,23] studied the effect of cerium pre-treatments on the corrosion behavior of aluminum composites. Results showed that direct cerium pretreatment slightly improved the surface protection against localized corrosion.…”
Section: Introductionmentioning
confidence: 96%